Group study vs. individual study a comparison of effective study technique. - Bang-as, Erlie P. & Toles, Elohai N.; Toles, Elohai N. (1998.)
This study was an attempt to find out which of the two study techniques is effective: group study or individual study. It also sought to know which of the two academic groups performed better in a group study or in an individual study. The respondents were 60 students from the Biological and Social Sciences Divisions. Subjects were selected using the simple random sampling. The design was a 2 ( Group study and Individual study) x 2 (Biological Sciences and Social Sciences) factorial design and this tested three hypotheses; (1) to find out if students perform better when they study in groups than when they study alone; (2) To find out if Biology students perform better than Social Sciences; (3) To know if Biology students perform better than Social Science students when they study in group/than when they study alone. The researchers used the 2 x 2 Analysis of Variance in the analysis of the data. The results were obtained by using the ANOVA and F test was used to test the hypotheses. The results revealed that (1) students who studied in groups performed better than those who studied individually; (2) Biology students performed better than Social Science students and (3) there was an interaction between study techniques and academic groups.
Thesis (Undergraduate, Bachelor of Arts in Psychology) College of Arts and Sciences, University of the Philippines in the Visayas, Miagao, Iloilo.
Keywords: Study technique -- Group; Study technique -- Individual